THE IMPORTANCE OF FORMATION OF LIFE SKILLS IN ENGLISH LANGUAGE CLASSES - Nazarova Mavluda (Journals Park Publishing, 2024)
The article "The Importance of Formation of Life Skills in English Language Classes" explores the integration of essential life skills into English language teaching, highlighting its significance in modern education. It emphasizes that language classes are not limited to linguistic competence but serve as platforms for developing crucial life skills such as communication, critical thinking, collaboration, adaptability, and empathy. The article outlines strategies for incorporating these skills, including project-based learning, role plays, debates, reflective writing, and authentic materials. It also discusses the broader benefits of this approach, including enhanced student motivation, holistic development, and better preparation for real-world challenges and future careers. By fostering these skills, English language classes contribute to the overall growth of students, making them more capable and adaptable in both personal and professional contexts.
Keywords: Life skills, English language teaching, communication skills, critical thinking, collaboration, adaptability, empathy, project-based learning, role plays, reflective writing, holistic development, real-world challenges, student motivation, language proficiency.